Play and learn : a study of online nutrition games and their effects on children's knowledge, attitudes and intentions. - Koh, Jing Jing. (2010)
This study examines the nature and effects of online nutrition games in promoting a healthy, balanced diet in children. As opposed to advergames, nutrition games are generally perceived as promoting healthful eating behaviours. Our study is concerned with the extent to which this is true. The first part of the study is a content analysis of 144 online nutrition games designed for children, whereby we examine the extent to which commercial and non-commercial games use persuasion and interactive strategies guided by health communication theories, as well as provide a balance of nutritional information. The findings of our first study show that there are significant differences in strategies employed by commercial and non-commercial games. Non-commercial games contained health messages that were more balanced in their presentation of all food groups and appropriate serving sizes compared to commercial games. Following our content analysis, the second part of our research presents an experimental study on the effects of balanced and unbalanced online nutrition games on children's knowledge, attitudes and intentions with parenting styles as an intervening factor.